Interplay Between Phosphorylation and O-GlcNAcylation of Sarcomeric Proteins in Ischemic Heart Failure - Mercier, Thomas; Bouvet, Marion; Dubois-Deruy, Emilie; Dechaumes, Arthur; Beseme, Olivia; Richard, Vincent; Mulder, Paul; Pinet, Florence (Frontiers in Endocrinology, 2018)
Post-translational modifications (PTMs) of sarcomeric proteins could participate to left ventricular (LV) remodeling and contractile dysfunction leading in advanced heart failure (HF) with altered ejection fraction. Using an experimental rat model of HF (ligation of left coronary artery) and phosphoproteomic analysis, we identified an increase of desmin phosphorylation and a decrease of desmin O-GlcNAcylation. We aim to characterize interplay between phosphorylation and O-GlcNAcylation for desmin in primary cultures of cardiomyocyte by specific O-GlcNAcase inhibition with thiamet G and silencing O-GlcNAc transferase and, in perfused heart perfused with thiamet G in sham- and HF-rats. In each model, we found an efficiency of O-GlcNAcylation modulation characterized by the levels of O-GlcNAcylated proteins and OGT expression (for silencing experiments in cells). In perfused heart, we found an improvement of cardiac function under O-GlcNAcase inhibition. But with none of the treatments either in in vitro or ex vivo cardiac models, we observe a modulation of desmin, phosphorylated and O-GlcNAcylated desmin expression, despite the presence of O-GlcNAc moities in cardiac desmin. Our data suggests no interplay between phosphorylation and O-GlcNAcylation of desmin in HF post myocardial infarction. The future requires finding the targets in heart involved in cardiac improvement under thiamet G treatment.